At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Our Q&A platform offers a seamless experience for finding reliable answers from experts in various disciplines. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Let's start by examining the given equation:
[tex]\[ \left(2^1\right)^n = \frac{2^x}{8^y} \][/tex]
First, simplify the left-hand side of the equation. Since [tex]\(\left(2^1\right)^n\)[/tex] is simply [tex]\(2^n\)[/tex], the equation becomes:
[tex]\[ 2^n = \frac{2^x}{8^y} \][/tex]
Next, simplify the right-hand side. Notice that [tex]\(8\)[/tex] can be expressed as a power of [tex]\(2\)[/tex]:
[tex]\[ 8 = 2^3 \][/tex]
Therefore, [tex]\(8^y\)[/tex] can be expressed as:
[tex]\[ 8^y = (2^3)^y = 2^{3y} \][/tex]
So, the equation now is:
[tex]\[ 2^n = \frac{2^x}{2^{3y}} \][/tex]
When dividing exponential expressions with the same base, you subtract the exponents:
[tex]\[ \frac{2^x}{2^{3y}} = 2^{x - 3y} \][/tex]
Now, the equation is:
[tex]\[ 2^n = 2^{x - 3y} \][/tex]
Since the bases are the same, we can set the exponents equal to each other:
[tex]\[ n = x - 3y \][/tex]
Thus, expressing [tex]\(n\)[/tex] in terms of [tex]\(x\)[/tex] and [tex]\(y\)[/tex], we have:
[tex]\[ n = x - 3y \][/tex]
[tex]\[ \left(2^1\right)^n = \frac{2^x}{8^y} \][/tex]
First, simplify the left-hand side of the equation. Since [tex]\(\left(2^1\right)^n\)[/tex] is simply [tex]\(2^n\)[/tex], the equation becomes:
[tex]\[ 2^n = \frac{2^x}{8^y} \][/tex]
Next, simplify the right-hand side. Notice that [tex]\(8\)[/tex] can be expressed as a power of [tex]\(2\)[/tex]:
[tex]\[ 8 = 2^3 \][/tex]
Therefore, [tex]\(8^y\)[/tex] can be expressed as:
[tex]\[ 8^y = (2^3)^y = 2^{3y} \][/tex]
So, the equation now is:
[tex]\[ 2^n = \frac{2^x}{2^{3y}} \][/tex]
When dividing exponential expressions with the same base, you subtract the exponents:
[tex]\[ \frac{2^x}{2^{3y}} = 2^{x - 3y} \][/tex]
Now, the equation is:
[tex]\[ 2^n = 2^{x - 3y} \][/tex]
Since the bases are the same, we can set the exponents equal to each other:
[tex]\[ n = x - 3y \][/tex]
Thus, expressing [tex]\(n\)[/tex] in terms of [tex]\(x\)[/tex] and [tex]\(y\)[/tex], we have:
[tex]\[ n = x - 3y \][/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.